Implementasi Konsep Kepemimpinan Kepala Madrasah dalam Meningkatkan Kinerja Guru dan Tenaga Kependidikan di Madrasah Ibtidaiyah Swasta (MIS) - Yoandi Putra Harahap; Sri Nurabdiah Pratiwi; Mhd. Isman (JoIEM (Journal of Islamic Education Management), 2024)
This study aims to examine the application of the leadership principles of madrasah principals in an effort to improve the performance of teachers and education personnel in Private Madrasah Ibtidaiyah (MIS). This research uses a qualitative approach. The results of this study show that madrasah principals are rated good based on annual evaluations from the Ministry of Religious Affairs of Simalungun Regency and North Sumatra Province. The performance of teachers and education personnel is also good, although there are shortcomings in terms of training or self-development to improve the efficiency of their duties. The madrasa principal's leadership proved effective in improving performance. The findings suggest teachers and education personnel should continue to improve the quality of teaching and learning evaluation to achieve madrasah goals. The theoretical implication is that effective leadership plays an important role in the progress of madrasah. The practical implication is that continuous improvement of learning quality and evaluation is necessary to achieve madrasah goals.